Changes in hormone receptor when breast cancer metastasizes to the colon: case report and literature review - Li, Huimeng; Yang, Liying; Sun, Xiqiang; Wang, Zhuquan; Qin, Shuangwei; Li, Chengcheng; Liu, Gongwu; Xie, Fengming; Gao, Weiwei (Frontiers in Oncology, 2025)
The metastasis of breast cancer to the colon is a rare occurrence, especially in the presence of changes in estrogen and progesterone receptors. To date, literature has only reported two cases of invasive ductal carcinoma and two cases of invasive lobular carcinoma metastasizing to the colon with concurrent changes in hormone receptors. This report describes a 65-year-old woman with a history of left breast cancer, who presented with symptoms of bloody stools and abdominal pain. CT and colonoscopy results revealed a malignant tumor in the ascending colon, and the patient underwent surgery. Pathological results post-surgery indicated changes in hormone receptors, differing from the previous breast cancer pathology, ultimately leading to the diagnosis of breast cancer metastasis to the colon. The patient was found to have liver metastasis 14 months after right hemicolectomy, and systemic metastases in various locations were discovered at the 19-month mark.